Linear Trifluoroethylamine RGD Peptidomimetics: Stereoselective Synthesis and Integrin αvβ3 Affinity - Piras, Monica; Fleming, Ian N.; Harrison, William T. A.; Zanda, Matteo (Synlett, 2012)
The Arg-Gly-Asp (RGD) tripeptide is the smallest recognition sequence for the αvβ3 integrin receptor. A number of nonpeptide analogues of the RGD linear sequence, some of them having improved pharmacological properties, have been proposed in the last two decades. In this study, the stereogenic trifluoroethylamine function was employed as peptide bond surrogate for the development of a new class of RGD peptide mimics. In fact, the trifluoroethylamine group was shown to behave as a peptide-bond surrogate maintaining the H-bond donor capacity of the NH peptide group and a CH(CF3)NH backbone angle close to the native peptide bond 120°. The trifluoroethylamine function is also known to display high metabolic stability and in some cases it positively affects ligand–receptor interactions. Two linear Ψ[CH(CF3)NH]Gly-RGD diastereoisomers were synthesized with good stereocontrol and submitted to biological assays. A remarkable loss in αvβ3 integrin affinity was observed for both compounds, suggesting that the bulky CF3 moiety is not well tolerated within the αvβ3 binding pocket.
Keywords: trifluoroethylamine; peptidomimetics; RGD; integrins